2005
DOI: 10.1086/496982
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Nonnucleoside Reverse-Transcriptase Inhibitors and Prevalence of HIV Type 1 Non-B Subtypes Are Increasing among Persons with Recent Infection in Spain

Abstract: The prevalence of drug resistance mutations was 12.1% among 198 persons who experienced human immunodeficiency virus (HIV) seroconversion identified in Spain during 1997-2004. There was a significant increase of K103N and of non-B subtypes over time. Transmission of HIV infection around the time of seroconversion was shown in 8 couples and in 2 clusters of 3 individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 14 publications
3
21
0
Order By: Relevance
“…11 They also were identified in 7.6% of recent HIV-1 seroconverters across our country. 13 In a prior report, we found that nearly two-thirds of HIV-1-infected immigrants in Las Palmas, the second largest island of the archipelago, were infected with non-B subtypes. 12 The objective of the current study was to assess the presence and nature of non-B subtypes in the native Spanish population newly diagnosed with HIV-1 infection in the island in the past 7 years.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…11 They also were identified in 7.6% of recent HIV-1 seroconverters across our country. 13 In a prior report, we found that nearly two-thirds of HIV-1-infected immigrants in Las Palmas, the second largest island of the archipelago, were infected with non-B subtypes. 12 The objective of the current study was to assess the presence and nature of non-B subtypes in the native Spanish population newly diagnosed with HIV-1 infection in the island in the past 7 years.…”
mentioning
confidence: 84%
“…In fact, more than 25 million are in sub-Saharan Africa 3 from where they are spreading to other regions, including industrialized countries of the northern hemisphere. 1,[5][6][7][8][9][10][11][12][13][14][15] The strong relationships with former African colonies and illegal entrance have both contributed to a sharp rise in the number of African immigrants arriving into the European Union during the past two decades. Due to its geographical position, one gate of entrance of Africans into Europe is Spain.…”
mentioning
confidence: 99%
“…In Spain, the large immigration wave seen during the past decade has been followed by an increased proportion of circulating non-B subtypes in the HIV population. 5,6 Periodic surveillance of drug resistance mutational patterns among drug-naive as well among treatment-experienced patients is important since selection of the most adequate first-line regimens as well as rescue interventions, respectively, may largely be influenced by this information.…”
Section: Introductionmentioning
confidence: 99%
“…Had this regimen been implemented on a wide scale without evaluation, significant resistance could have developed in the population. This, in turn, would lead to transmission of resistance mutations into populations never treated with antiretroviral agents as has been demonstrated in the US and Europe [2,3]. With limited drug formularies, transmission of drug resistance to nonnucleoside reverse transcriptase inhibitors or cytosine nucleoside analogs could lead to a lack of available treatment options for newly diagnosed HIV infected individuals in many regions.…”
Section: Commentarymentioning
confidence: 99%